SOCIO-PSYCHOLOGICAL ASPECTS OF SEX EDUCATION (Хабаршы. Психология және социология сериясы, 2023)
Sexual health education is a contentious issue in the Kazakh context. Although the importance of sex education for adolescents is well known in various societies, in Kazakhstan it remains controversial due to the conflict associated with cultural, religious and traditional ideas. Moreover, there is concern in society that teenagers will have sex as a result of sex education. The topic of sex education has divided our society, where some are in favor of sex education, while others are against it. In this regard, this article provides an overview analysis regarding the need for sex education in Kazakhstan. The importance of applying a holistic approach to sex education, which includes a social, psychological and biological aspect, is also considered. Relevant articles and materials for analysis were collected from Science Direct, Google Scholar, Elsevier, Citeseer, PubMed, Web of Science, Scopus search engines after applying inclusion and screening criteria. The results of the study show that the lack of a comprehensive and effective sexual education directly affects the psychological processes of the individual and leads to social problems at the macro level.Keywords: sex education, sexual and reproductive health, socio-psychological aspects of sex education.